Electric Double Layered Magnetic Fluids (EDL-MF) based on spinel ferrite nanostructures [(M1-x+2Fex+3)]A [(Fe2-x+3 Mx+2)]BO4-2 - Tourinho, F.A. (1998)
This paper presents a review of Electric Double Layered Magnetic Fluids (EDL-MF) based on spinel ferrite type [(M1-x+2Fex+3)]A [(Fe2-x+3 Mx+2)]BO4-2, with M(II) = Mn, Co, Ni, Cu and Zn. The chemical synthesis of the nanoparticles using hydrothermal techniques and their complete peptization in an aqueous medium results in a ultra stable magnetic colloid, EDL-MF. The characterization of the particles was performed using X-ray diffraction and electronic microscopy techniques. The resulted sols were investigated by magnetic, magneto-optical measurements and magnetic resonance techniques.